Culture in Historical Narration - Czyrka, Marek (Roczniki Kulturoznawcze, 2010)
The goal of the publication is to discuss the cultural dimension of historical narration. The subject of the consideration includes the following research issues: the humanities related to the subject matter of human and culture; relation of different forms of dynamics of historical process taking into consideration the gradual development and the contrasted explosion moment; the objective way applied by the researcher and constructing some facts with the use of self-knowledge mechanisms. It was determined that historiography can be identified with the science of culture. Historical research can present culture and history in the form of an organized or unorganized field. The article is summarized with conclusions.